Traditional medicine in China for ischemic stroke: bioactive components, pharmacology, and mechanisms - Min Xu; Rui-Xia Wu; Xiao-Li Li; Yi-Shen Zeng; Jia-Yang Liang; Ke Fu; Yuan Liang; Zhang Wang (Journal of Integrative Neuroscience, 2022)
Ischemic stroke is an acute cerebrovascular disease and the third most common cause of death after ischemic heart disease. Increasing attention is being paid to finding effective treatments through traditional medicine. Thus, studying the traditional medicine for the treatment of ischemic stroke is of great importance. Traditional medicine in China includes traditional Chinese medicine (TCM) and other ethnic medicines, which is rich in variety and resources. This review first introduces the treatment mechanisms associated with ischemic stroke, such as antioxidant nitrification, antiexcitotoxic, antiapoptotic, anti-inflammatory, antiplatelet and anticoagulation mechanisms. Then, we calculated the frequency of prescription use for ischemic stroke and summarized the treatments for ischemic stroke by investigating 13 drug monographs and standards. We found 192 prescriptions from the traditional medical system for ischemic stroke, including Angong Niuhuang pill, Qishiwei Zhenzhu Pills, Ginkgo biloba leaf, and other traditional Chinese patent medicines and national medicines. There were 398 kinds of traditional medicine, including 301 kinds of plant-based medicines, 54 kinds of animal-based medicines, 28 kinds of mineral-based medicines, and 15 kinds of other medicines. We introduced the names, families, medicinal components, traditional uses, phytochemical information, and pharmacological activities of the commonly used Chinese patent medicines and TCMs. In addition, some chemicals were introduced. These medicines may be potential candidates for the treatment of ischemic stroke. This work provides a reference for the research and clinical use of new drugs for ischemic stroke.